Analisis Pengaruh Kepuasan Masyarakat Transparansi Dan Akuntabilitas Terhadap Kebijakan Pelayanan - Ermawiningsih, Sri; Miftah, Miftahul (Otonomi, 2025)
The purpose of this research is to know and analyze the influence of community satisfaction, transparency and accountability of the policies the services in the Bago District Tulungagung Urban Village. This research using descriptive quantitative methods. With a population of urban village society in Bago, using samples with 100 respondents. Data collection method using a questionnaire, literature and methods of observation field. According to an analysis of data using multiple linear regression analysis. The results of this study show that people's satisfaction, transparency and accountability for the policy of service in the area of Bago, Tulungagung District has a significant effect. It is supported by the result of r square or coefficient determination (kd ) shows 76.3 % so interpreted if variable x1 (civilization ), x2 (transparency ) and x3 (accountability ) have contributions of 76.3 % to variable y (service policy ) and other 23.7 %s affected by other factors other than variable x. In addition, in the f count 107,219 receive is worth of 0,000 sig. Thus showing that the f count greater than f table or 107,219 > 2,70 with the sig 0,000< 0,05 .Thus received hypothesis. While on the outcome of the t known for partial community satisfaction that, transparency and accountability of the policies the services in the Bago District Tulungagung significant urban village.